Analysis of Factors Affecting the Level of Knowledge of Health Personnel about Vaccine Management - Truly Dian Anggraini; Retnowati Adiningsih (Indonesian Journal of Global Health Research, 2022)
Drug storage is a series of activities that aim to store and maintain drugs or pharmaceutical preparations by placing stock of drugs or pharmaceutical preparations in a place that is considered safe. In a study conducted by Lestari in 2017, it was found that expired and damaged drugs at Benyamin Galuh Hospital were 5.79% (Lestari, 2017). Drug damage can cause negative effects that can harm the patient. In addition to storage, it is also necessary to have knowledge of qualified health personel because it is the final storage place for vaccines before they are given to patients. The aim of this research is This study aims to determine the factors that influence the level of knowledge of health personel at Karangmalang Health Center regarding vaccine management. This research is a cross- sectional type of analytical research, by distributing questionnaires and then analyzed descriptively about each respondent's characteristics and analyzed for predictor factors. The population of this study was taken from the population of health personel who work at the Karangmalang Public Health Center, Sragen. The sample used was 69 health personel consisting of medical and non-medical personnel. The results of the questionnaire distributed to 69 health personel at the Karangmalang Public Health Center, Sragen, 79.71% were in the good knowledge category. In this case, if the vaccine preparation has good quality or is damaged, the vaccine will be inefficient. Therefore, it is necessary to have sufficient knowledge of health personel to maintain the quality of vaccine preparations. The results of the analysis show that the predictor factors that affect the level of knowledge of Health personel about vaccine management at the Karangmalang Health Center, Sragen, are the level of education and age. Knowledge level has a strong relationship with education level of 0.564 and age of 0.605. If the level of education increases, the level of knowledge will increase by 0.723 times as well as increasing age, the level of knowledge will increase by 1.6 times.